Isometric Midthigh Pull Characteristics in Elite Youth Male Soccer Players: Comparisons by Age and Maturity Offset. Issue 10 (October 2020) - Morris, Rhys O.; Jones, Ben; Myers, Tony; Lake, Jason; Emmonds, Stacey; Clarke, Neil D.; Singleton, Dave; Ellis, Matthew; Till, Kevin
Abstract : Abstract: Morris, RO, Jones, B, Myers, T, Lake, J, Emmonds, S, Clarke, ND, Singleton, D, Ellis, M, and Till, K. Isometric midthigh pull characteristics in elite youth male soccer players: Comparisons by age and maturity offset. J Strength Cond Res 34(10): 2947–2955, 2020—The purpose of this study was to (a) provide comparative isometric midthigh pull (IMTP) force-time characteristics for elite youth soccer players and (b) determine the effect of age and maturation on IMTP force-time characteristics. Elite male youth soccer players (U12 n = 51; U13 n = 54; U14 n = 56; U15 n = 45; U16 n = 39; and U18 n = 48) across 3 maturity offset groups (Pre n = 117; circa n = 84; and Post–peak height velocity n = 92) performed 2 maximal IMTP trials on a portable force platform (1, 000 Hz). Absolute and relative values for peak force (PF) and impulse over 100 and 300 ms were analyzed. A full Bayesian regression model was used to provide probable differences similar to that of a frequentist p value. Advanced age and maturation resulted in superior IMTP force-time characteristics. Peak force demonstrated high probabilities of a difference between all consecutive age groups ( p > 0.95). For absolute and relative impulse (100 and 300 ms), only 2 consecutive age groups (U14–15's and U16–18's) demonstrated high probabilities of a difference ( p > 0.95) with large effects ( d = 0.59–0.93). There were high probable differences between all maturity offset groups for PF and impulse with medium to large effects ( d = 0.56–3.80). These were also reduced when expressed relative to body mass (relative PF and relative impulse). This study provides comparative IMTP force-time characteristics of elite male youth soccer players. Practitioners should consider individual maturation status when comparing players given the impact this has on force expression.